2012
DOI: 10.1007/s00417-011-1910-7
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal observations in Vogt–Koyanagi–Harada disease using high-penetration optical coherence tomography

Abstract: Significant choroidal thickness changes underlie VKH disease, which progress over time. Objective measurement of the choroidal thickness using HP-OCT may be useful for longitudinal evaluation of VKH activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 20 publications
(35 reference statements)
8
80
1
3
Order By: Relevance
“…In patients with acute VKH disease, EDI-OCT images clearly showed bilateral diffusely thickened choroids that decreased over time with corticosteroid treatment [4][5][6]. In the current case, we clearly visualized the full-thickness choroid except in the untreated phase and the decreasing choroidal thickness during tapering of oral prednisolone.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In patients with acute VKH disease, EDI-OCT images clearly showed bilateral diffusely thickened choroids that decreased over time with corticosteroid treatment [4][5][6]. In the current case, we clearly visualized the full-thickness choroid except in the untreated phase and the decreasing choroidal thickness during tapering of oral prednisolone.…”
Section: Discussionsupporting
confidence: 49%
“…However, Nakai et al [6] reported that a SRD developed again in four eyes with anterior inflammation and the choroidal thickness again increased markedly. The choroid appears to be primarily affected in VKH disease initially; therefore, rebound choroidal thickening seen on EDI-OCT images could be regarded as recurrent VKH disease, as in the current case, despite no clinical evidence of recurrent ocular inflammation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…25 Several groups have described reversal of choroidal thickening, and even atrophy, in patients with VKH disease following treatment. [26][27][28][29][30] Hessen et al described a 58-year-old black woman who developed a painless 6 Â 7 mm scleral nodule underneath normal appearing conjunctiva with no clinical evidence of scleral inflammation. 21 At the time of biopsy, the lesion was found to arise from the sclera and to involve the insertion of the medial rectus muscle.…”
mentioning
confidence: 99%